High nutrition literacy linked with low frequency of take-out food consumption in chinese college students - Qi Qi; Qing Sun; Ling Yang; Yan Cui; Jing Du; Huaqing Liu (BMC, 2023)
Abstract Background The excessive consumption of take-out food has increased the risk of nutrition-related chronic diseases. Nutrition literacy (NL) is an important influencing factor of food choice. This study aimed to explore the relationship between nutrition literacy and take-out food consumption. Methods A cross-sectional study was conducted on 2130 college students in Bengbu, China. A self-reported questionnaire that included demographic information, lifestyle behavior, take-out food consumption, and nutrition literacy scale was used. Ordinal logistic regression models were used to analyze the association between nutrition literacy and take-out food consumption. Results Of the students surveyed, 61.5% consumed take-out food at least once a week. NL was significantly associated with the frequency of take-out food consumption ≥ 4 times/week (OR = 0.995, 95% CI = 0.990-1.000); the difference specifically was discovered for applying skills, interactive skills, and critical skills. Moreover, students with high level NL ate less (Spicy) hot pot (OR = 0.996, 95% CI = 0.992-1.000), but more vegetable and fruit salad (OR = 1.009, 95% CI = 1.002-1.015). Conclusions NL, especially in applying skills, interactive skills, and critical skills, is not only associated with consumption frequency of take-out food among college students, but also links with types of take-out food consumption. Our findings emphasize that targeted interventions on nutritional skills literacy should be needed to improve dietary behaviors for student's good health.